Walking together: a decolonising experiment in bushfire management on Dja Dja Wurrung country. (July 2019) - Neale, Timothy; Carter, Rodney; Nelson, Trent; Bourke, Mick
Within certain settler colonial nations, Indigenous peoples are increasingly becoming present and influential in the agencies legally responsible for the management of their ancestral territories, their environments and their hazards. On the Australian continent, for example, Aboriginal peoples are becoming more formally involved in the management of bushfire (or 'wildfire' elsewhere). This environmental phenomenon is at once of profound cultural significance to many Aboriginal peoples and a major natural hazard to human life and property, managed by an extensive professional bureaucracy of settler government agencies. Drawing upon a case study of collaborative bushfire management between Dja Dja Wurrung peoples and settler bushfire management agencies on Dja Dja Wurrung country (or, ancestral territory) in the southeast Australian state of Victoria, this article argues for an understanding of such collaborations as 'decolonising experiments'. For geographers and others, this means paying attention to the open-ended character of collaborative initiatives, whether and how they materially improve the position of Indigenous peoples, as well as whether and how they give rise to new resources and strategies for the creation of other decolonising futures.